Performance Analysis and Optimisation of an Oil Natural Air Natural Power Transformer Radiator. (2016) - Anishek, S.; Sony, R.; Jayadeep Kumar, J.; Kamath, Pradeep M.
Abstract: In Power transformers are inevitable components in alternating current generation, transmission, distribution and utilization systems. Lifespan and performance of power transformer are dependent on cooling system employed for dissipation of heat generated during its operation. In this paper numerical simulation of an oil natural air natural power transformer radiator was performed to determine its cooling capacity. In addition, optimum spacing between sections and optimum length of sections of radiator were also determined. An optimised radiator design was proposed and was simulated to determine its cooling capacity. The proposed radiator design was found to 14% more efficient than existing design in terms of cooling capacity for same material cost. The control volume method has been used to resolve the continuity, the momentum and the energy equations in steady state.